Charismatic leadership: Beyond love and hate and toward a sense of belonging?. (21st May 2019) - Parry, Ken; Cohen, Michael; Bhattacharya, Sukanto; North-Samardzic, Andrea; Edwards, Gareth
Abstract: Developing previous work on charismatic leadership by Boas Shamir and Ken, we investigate the contention that followers of charismatic leaders have an emotional connection with that leader in the form of a 'sense of belonging' and links to community. We, therefore, investigate whether there is any evidence of a sense of belonging when people describe those they judge to be charismatic. Using a mixed-methods aesthetic narrative approach, we are able to supply empirical support for the existence of such a relationship and to extend the findings of previous studies by incorporating the connection that the leader has with the community, in general, as an important factor in the leader–follower relationship.